Convergencia real en Europa Central y del Este: un análisis del período 1950-2008 - Cuñado, Juncal; Rodríguez-Tejedo, Isabel (Papeles de Europa, 2010)
This article examines the real convergence hypothesis for the period 1950-2008 in some Central and Eastern European countries using time series techniques and allowing for structural breaks. We find convergence within the countries when applying unit root tests on per capita GNP differences, but not when per capita GNP differences are defined with respect to Germany, the point of reference for the EU. However, when we allow for the existence of structural breaks in the convergence process, we find evidence of some countries (Albania, Bulgaria, former Czechoslovakia) catching-up with the German economy since the nineties. This suggests that the changes taking place since then in those countries have had a positive impact on convergence.
Keywords: Real convergence; Central and Eastern Europe; Unit roots; European Union